Interpretation of the Expansion of the Application of the Authority of the State Administrative Court in Adjudicating Factual Legal Actions of the Government - Andrianantenaina Fanirintsoa Aime; PradistyaPurnama Aji (Universitas Negeri Semarang, 2023)
The evolution of the State Administrative Court’s authority in adjudicating factual legal actions involving government entities represents a dynamic facet of administrative law. This paper aims to explore and interpret the nuanced expansion of the State Administrative Court’s jurisdiction in handling cases related to factual legal actions initiated by the government. Through an in-depth analysis of legal precedents, legislative developments, and judicial interpretations, the study navigates the evolving landscape of administrative law. The paper delineates the historical context and legal frameworks that have shaped the State Administrative Court's jurisdiction, emphasizing its pivotal role in ensuring governmental accountability. It investigates the implications of the broadened scope of authority on the court's adjudicative processes and the overall legal landscape. Furthermore, the research scrutinizes key cases to illustrate how the court’s expanded jurisdiction impacts the resolution of factual legal actions involving government entities. By examining the interplay between legislative intent, judicial reasoning, and practical implications, the paper provides insights into the complexities and challenges associated with this expanded mandate. The findings underscore the significance of a judicious balance between the State Administrative Court’s authority and the imperative to maintain government efficacy. Additionally, the paper contributes to the ongoing discourse on administrative law by offering a comprehensive interpretation of the expanding role of the State Administrative Court in the adjudication of factual legal actions initiated by the government. In conclusion, this paper enhances our understanding of the evolving dynamics within administrative law, shedding light on the implications and intricacies surrounding the State Administrative Court’s extended authority in addressing factual legal actions involving government entities.